2020
DOI: 10.1080/03634523.2020.1857417
|View full text |Cite
|
Sign up to set email alerts
|

More than just a variable: COVID-19 and the call to complicate communication education research

Abstract: The coronavirus pandemic brought to light the numerous challenges faced by students that are often not considered in the classroom (e.g., food/housing insecurity, limited Internet access). The rapid transition to online learning shattered the perception that the classroom is independent of greater societal and institutional contexts. Shifting courses online midsemester brought into focus various inequities present in higher education and how they influence students' experiences in the teaching/learning process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…An initial analysis conducted early into the data collection efforts for the present study showed that two such factors associated with greater loneliness were living alone and not being in a committed romantic relationship ( Ray, 2021 ). However, in the months since that initial analysis occurred, relationships ended ( Lebow, 2020 ), new relationships began ( Wiederhold, 2021 ), and living arrangements changed, sometimes unexpectedly—all during a global pandemic ( Ashby-King, 2021 ). Thus, this study investigated both the trajectory of loneliness over the course of the first year of the pandemic for adults in the United States, and also whether changes in one’s romantic relationships status or living arrangements predicted changes in loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…An initial analysis conducted early into the data collection efforts for the present study showed that two such factors associated with greater loneliness were living alone and not being in a committed romantic relationship ( Ray, 2021 ). However, in the months since that initial analysis occurred, relationships ended ( Lebow, 2020 ), new relationships began ( Wiederhold, 2021 ), and living arrangements changed, sometimes unexpectedly—all during a global pandemic ( Ashby-King, 2021 ). Thus, this study investigated both the trajectory of loneliness over the course of the first year of the pandemic for adults in the United States, and also whether changes in one’s romantic relationships status or living arrangements predicted changes in loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these concerns, discussions on and experiments with alternatives to traditional grading are beginning to flourish. In some cases, these efforts seem to have been redoubled by the COVID-19 pandemic (Ashby-King, 2021; Goldrick-Rab, 2021; Veletsianos and Houlden, 2020), which also played a role in increasing student stress and anxiety (Aslanian and Roth, 2021; Greenberg, 2021). But even before the pandemic, several liberal arts colleges and elite institutions such as Brown University have allowed students to opt for a pass/fail rather than graded system in individual courses.…”
Section: Literature Reviewmentioning
confidence: 99%